2006
DOI: 10.1128/jvi.80.7.3322-3331.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Peptide-Binding and ATPase Domains of Recombinant hsc70 Are Required To Interact with Rotavirus and Reduce Its Infectivity

Abstract: The heat shock cognate protein hsc70 has been implicated as a postattachment cell receptor for rotaviruses. Here we show that hsc70 interacts specifically with rotaviruses through its peptide-binding domain, since a recombinant full-length hsc70 protein and its peptide-binding domain, but not its ATPase domain, bound triple-layered particles in a solid-phase assay, and known ligands of hsc70 competed this binding. The peptide ligands of hsc70 were also shown to block rotavirus infectivity when added to cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 49 publications
1
42
0
1
Order By: Relevance
“…132 However, it has been shown that Hsc70 retains its substrate binding capacity in the absence of ATPase activity; 133 the intact peptide-binding domain of sHsc70 would thus be expected to be functional as a binding protein.…”
Section: Autophagosomal Membrane Proteinsmentioning
confidence: 99%
“…132 However, it has been shown that Hsc70 retains its substrate binding capacity in the absence of ATPase activity; 133 the intact peptide-binding domain of sHsc70 would thus be expected to be functional as a binding protein.…”
Section: Autophagosomal Membrane Proteinsmentioning
confidence: 99%
“…Several integrin family members (␣ 2 ␤ 1 , ␣ 4 ␤ 1 , ␣ x ␤ 2 , and ␣ V ␤ 3 ) play a role in attachment and postattachment events in vitro (28,30,42) but may not all be essential for entry (36,42). In addition, the heat shock protein hsc70 has also been implicated in late entry events and changes in the RV particle (31,49). However, the cell surface receptors involved in viral entry in vivo, either in the gut or elsewhere, have not been well characterized.…”
mentioning
confidence: 99%
“…Studies have shown that Hsc70 can initiate the disassembly of oligomeric protein complexes (18). Also as described above, Hsp70 and Hsc70 have been found to have roles in inducing conformational change in viral capsids which is then followed by entry and uncoating in cells (21,47). We hypothesize that Hsc70-2 induces a conformational change in CNV capsids which may contribute to disassembly of particles in the cytoplasm.…”
Section: Resultsmentioning
confidence: 99%